2021
DOI: 10.1136/jech-2020-214841
|View full text |Cite
|
Sign up to set email alerts
|

How does income affect mental health and health behaviours? A quasi-experimental study of the earned income tax credit

Abstract: BackgroundAlthough research has repeatedly demonstrated the association between poverty, mental health, and health behaviours, there is limited evidence on the effects of interventions to improve these outcomes by addressing poverty directly. Moreover, most prior studies are often confounded by unobserved characteristics of individuals, making it difficult to inform possible interventions. We addressed this gap in the literature by leveraging quasi-random variation in the earned income tax credit (EITC)—the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
(21 reference statements)
2
21
0
Order By: Relevance
“…According to a randomized household survey conducted in Montreal in 2009, employment status under 45-year-old is inversely related to the distress and depression, using coping strategies like social support and alcohol usage [24]. In a study conducted using a sample taken from Panel Study of Income Dynamics [25], they estimated the association between estimated income tax credit (EITC) and income and other outcomes of interest like smoking, alcohol intake, physiological distress, and overall health. They found that people with high income are associated with less physiological distress, more alcohol consumption, more cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…According to a randomized household survey conducted in Montreal in 2009, employment status under 45-year-old is inversely related to the distress and depression, using coping strategies like social support and alcohol usage [24]. In a study conducted using a sample taken from Panel Study of Income Dynamics [25], they estimated the association between estimated income tax credit (EITC) and income and other outcomes of interest like smoking, alcohol intake, physiological distress, and overall health. They found that people with high income are associated with less physiological distress, more alcohol consumption, more cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher income is associated with decreasing of psychological distress and psychological distress may influence the occurrence of depressive symptoms. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Poverty is associated with increased psychological stress and is suggested to reduce a person's "cognitive band width." This can contribute to poor decision making which can impact their health through engagement in risky behaviours [6]. In contrast, when the case data is accumulated by the local authority area, the data did not look as convincing in relation to this.…”
Section: Socioeconomicsmentioning
confidence: 95%
“…It seems that the intended benefit foreseen from these referrals would be the diagnosis of an underlying mental health condition and the prevention of a future recurrence. The impact of poverty on physical and mental well-being is well recognised, with lower incomes particularly predisposing individuals to greater risk of a mental health illness [6]. There is scarce discussion in the literature regarding an association between poverty or socioeconomic deprivation and the problem of an entrapped rectal foreign body.…”
Section: Introductionmentioning
confidence: 99%